Cometary grains in the HD 32297 debris disk. Issue 7 (July 2016) - Yang, Y.-G; Li, Aigen
Abstract: HD 32297 is a young A-type star with a bright edge-on debris disk. The dust thermal emission spectral energy distribution and scattered starlight spectrum are simultaneously modeled in terms of porous cometary grains. Our modeling suggests that, similar to the solar system, the debris disk around HD 32297 may have an inner warm ring and an outer cold disk which are seen in other young debris disks as well.